Comparing the National Institutes of Health Stroke Scale Scores between emergency medicine physicians and neurologists for timely decision-making for alteplase administration - Osman Tecir; Mustafa Çiçek; Özgen Gönenç Çekiç; Şenol Ardıç; Ramazan Akpınar; Nuray Can Usta; Süleyman Türedi (Turkish Journal of Emergency Medicine)
OBJECTIVES: The National Institutes of Health Stroke Scale (NIHSS) is used to determine the severity of the disease and to make treatment decisions in ischemic stroke patients. However, the need for a neurologist to assess NIHSS before thrombolytic therapy may prolong the treatment process. METHODS: This prospective, single-center, observational, planned study included patients who presented to the emergency department in the first 24 h after the onset of symptoms and were diagnosed with ischemic stroke between September 2022 and June 2023. The NIHSS was evaluated by the emergency medicine physicians and neurologists who evaluated the patients in the emergency department, and the decisions on whether to administer thrombolytics and the time taken for this decision were recorded and compared. RESULTS: A very high agreement was found when the total NIHSS scores of emergency medicine physicians and neurologists were compared (intraclass correlation coefficient = 0.947 [95% confidence interval 0.92–0.96]). Emergency medicine physicians and neurologists showed high agreement with thrombolytic therapy decisions. In patients given thrombolytic therapy, emergency medicine physicians made the decision earlier than neurologists, and there was a significant difference of 14 ± 12 min between the decisions of emergency physicians and those of neurologists. CONCLUSIONS: There is high agreement between emergency medicine physicians and neurologists in the NIHSS evaluation and thrombolytic decisions for patients with acute ischemic stroke. According to our results, emergency medicine physicians can provide thrombolytic treatment in accordance with neurologists, thus shortening the time for thrombolytic treatment.